Marcelle Capy and the Pacifist Female Voices Amidst the Conflict - Cecilia Benaglia (Studies in 20th & 21st Century Literature, 2017)
This article analyses the writings of French writer and journalist Marcelle Capy (1891–1962), who held an uncommon position in the French intellectual field throughout the First World War. Going against the mainstream French feminist groups, who all prioritized loyalty to the fatherland over pacifism, Capy remained faithful to her socialist and anti-war creed. Although little known to the larger French public, Capy’s double marginality as a woman and as a pacifist makes her work a singular testimony of the war years as well as a significant example of the rejection of the national climate and Union sacrée’s rhetoric. In the first section of this article, I will locate Capy in the national context, within the spectrum of attitudes adopted by female activists. I will then focus on her writings, studying in particular her text Une Voix de femme dans la mêlée ('A Woman’s Voice Amidst the Conflict'). I argue that the strength of her criticism stems from her use of narrative, rather than from political-theoretical analyses. The short stories that compose the majority of her writings, presented as pieces of direct and “non-manipulated” testimony, offer a counter-point to national narratives and an attempt to defamiliarize the public perception of World War I.
Keywords: women and WWI; pacifism; journalism; Marcelle Capy